2013
DOI: 10.1515/jcim-2012-0002
|View full text |Cite
|
Sign up to set email alerts
|

First report of fingerprinting dried herbal products using a subtractive diversity array

Abstract: This technique provides a new way to produce markers for authenticating dried herbal samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…ma-yuen Stapf), is a TCM widely recognized for its rich nutritional and medicinal value. Fingerprinting of Coicis semen from dried tissues using the sequence-independent microarray ( Niu et al, 2013 ) and the high-performance liquid chromatography (HPLC)-evaporative light scattering detector ( Du et al, 2021 ) has been reported. It contains more than 80 active components including polysaccharides, fatty acids (FAs), phenolic acids, sterols, lipids, flavonoids, triterpenes, alkaloids, and adenosine ( Zhu, 2017 ; Yu J. et al, 2022 ; Huang et al, 2022 ; Pan et al, 2023 ; Wei et al, 2023 ).…”
Section: The Cardiovascular Protective Activity Of Yyfzmentioning
confidence: 99%
“…ma-yuen Stapf), is a TCM widely recognized for its rich nutritional and medicinal value. Fingerprinting of Coicis semen from dried tissues using the sequence-independent microarray ( Niu et al, 2013 ) and the high-performance liquid chromatography (HPLC)-evaporative light scattering detector ( Du et al, 2021 ) has been reported. It contains more than 80 active components including polysaccharides, fatty acids (FAs), phenolic acids, sterols, lipids, flavonoids, triterpenes, alkaloids, and adenosine ( Zhu, 2017 ; Yu J. et al, 2022 ; Huang et al, 2022 ; Pan et al, 2023 ; Wei et al, 2023 ).…”
Section: The Cardiovascular Protective Activity Of Yyfzmentioning
confidence: 99%